2022
DOI: 10.3389/fevo.2022.929266
|View full text |Cite
|
Sign up to set email alerts
|

Orchid diversity along an altitudinal gradient in the central Balkans

Abstract: Understanding patterns of species diversity along an altitudinal gradient is the major topic of much biogeographical and ecological research. The aim of this study was to explore how richness and density of orchid species and subspecies in terms of different categories of underground organ systems and pollination systems vary along an altitudinal gradient in the central Balkans. The altitudinal gradient of the study area was divided into 21 100-m vertical intervals. Data were analyzed using both non-linear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Although their small seeds make them good dispersers, these islands may not provide the environmental conditions required for these species to stabilize permanently. Our findings are consistent with previous research indicating that elevation is a recognized predictor of orchid richness (Ackerman et al., 2007; Djordjević et al., 2022). This relation is particularly strong for both autogamous and rewarding groups indicating an altitudinal gradient on Mediterranean islands as well as supporting what has been found in both insular and continental contests (Djordjević et al., 2022; Jacquemyn et al., 2005).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although their small seeds make them good dispersers, these islands may not provide the environmental conditions required for these species to stabilize permanently. Our findings are consistent with previous research indicating that elevation is a recognized predictor of orchid richness (Ackerman et al., 2007; Djordjević et al., 2022). This relation is particularly strong for both autogamous and rewarding groups indicating an altitudinal gradient on Mediterranean islands as well as supporting what has been found in both insular and continental contests (Djordjević et al., 2022; Jacquemyn et al., 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previous research indicating that elevation is a recognized predictor of orchid richness (Ackerman et al., 2007; Djordjević et al., 2022). This relation is particularly strong for both autogamous and rewarding groups indicating an altitudinal gradient on Mediterranean islands as well as supporting what has been found in both insular and continental contests (Djordjević et al., 2022; Jacquemyn et al., 2005). This pattern can be explained by the fact that these syndromes are very often associated with meadows and forests dominated by Quercus ilex which occur on the most elevated islands very often as remnant of an intense human impact at lower elevations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Orchids (epiphytes and terrestrial) are important components of tropical forests [29,30] and have important roles in the total biomass, water balance, and nutrient cycling of ecosystems [30,31]. Due to their ecological significance, orchids have been used for several years as indicators of environmental changes related to land use [32,33], forest disturbance [23,34], or the effects of environmental factors, such as elevation [35][36][37][38]. In this context, the main findings suggest a bell-shaped distribution of species richness with elevation [30,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their ecological significance, orchids have been used for several years as indicators of environmental changes related to land use [32,33], forest disturbance [23,34], or the effects of environmental factors, such as elevation [35][36][37][38]. In this context, the main findings suggest a bell-shaped distribution of species richness with elevation [30,[34][35][36][37][38]. Following this pattern for Ecuador, Küper et al [39] showed a bell-shaped elevational pattern of orchid richness.…”
Section: Introductionmentioning
confidence: 99%